2013
DOI: 10.1016/j.bbamcr.2013.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin phosphorylation and assembly are regulated by the small GTPase Rab7a

Abstract: Intermediate filaments are cytoskeletal elements important for cell architecture. Recently it has been discovered that intermediate filaments are highly dynamic and that they are fundamental for organelle positioning, transport and function thus being an important regulatory component of membrane traffic. We have identified, using the yeast two-hybrid system, vimentin, a class III intermediate filament protein, as a Rab7a interacting protein. Rab7a is a member of the Rab family of small GTPases and it controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(89 citation statements)
references
References 71 publications
4
85
0
Order By: Relevance
“…Co-immunoprecipitation of endogenous proteins in HeLa cells was performed using a crosslink immunprecipitation kit (Pierce, Rockford, IL), following the manufacturer's instructions and as described previously (Cogli et al, 2013a).…”
Section: Co-immunoprecipitation Pull-down and Direct Interaction Expmentioning
confidence: 99%
“…Co-immunoprecipitation of endogenous proteins in HeLa cells was performed using a crosslink immunprecipitation kit (Pierce, Rockford, IL), following the manufacturer's instructions and as described previously (Cogli et al, 2013a).…”
Section: Co-immunoprecipitation Pull-down and Direct Interaction Expmentioning
confidence: 99%
“…We demonstrated that the interaction is direct and that Rab7a regulates vimentin and peripherin filament assembly [17,18]. Overexpression of Rab7a wt or expression of the constitutively active Rab7a Q67L mutant protein increased vimentin phosphorylation and caused redistribution of vimentin in the soluble fraction, while, coherently, Rab7a-depletion determined a decreased phosphorylation of vimentin and increased the amount of filamentous vimentin [17,18].…”
Section: Introductionmentioning
confidence: 95%
“…In fact, vimentin regulates Rac1 activation while activation of Rac1 induces vimentin phosphorylation and disassembly [51][52][53][54]. Furthermore, we have previously shown that Rab7a interacts with vimentin and that depletion of Rab7a determines a lower phosphorylated state of the head domain of vimentin and a higher abundance of vimentin in the insoluble, filamentous fraction [17]. As both Rab7a and Rac1 regulate vimentin assembly and since it has previously been shown that vimentin filaments are oriented towards the leading edge during migration [55], we tested whether vimentin filament orientation was impaired in Rab7a-depleted cells in a wound healing assay.…”
Section: Rab7a Regulates Vimentin Filaments Orientation During Cell Mmentioning
confidence: 99%
See 1 more Smart Citation
“…There is accumulating evidence that the organization of intermediate filaments is regulated by phosphorylation. Changes in the phosphorylation of the intermediate filaments have been suggested as a potential mechanism to modulate their assembly and distribution (Steinert et al, 1993;Sin et al, 1998;Valgeirsdóttir et al, 1998;Satelli and Li, 2011;Cogli et al, 2013). Using immunofluorescence analyses, we found that enoxaparin 1 gefitinib treatment redistributed p-vimentin to the perinuclear area.…”
Section: Sensitization Of Lung Cancer Cells By Enoxaparin To Gefitinibmentioning
confidence: 79%